A new fundamental research of pilgrimage prose in the 1800s–1860s [Book Review: Alexandrova-Osokina O.N. Pilgrimage Prose of the 1800s and 1860s: Sacred Space, History, Human. Moscow, Flinta, Nauka, 2015] - N.G. Komar (Ученые записки Казанского университета: Серия Гуманитарные науки)
The review considers the monograph “Pilgrimage Prose of the 1800s and 1860s: Sacred Space, History, Human” by O.N. Alexandrova-Osokina, the authoritative researcher of pilgrimage literature, published in 2015. Pilgrimage literature is a comprehensive phenomenon that emerged in Russia along with the adoption of Christianity, represented by a variety of genres and reflecting the most important facet of the national culture, i.e., the practice of pilgrimage. By the middle of the 19th century, there was not only the prosperity of pilgrimage prose in the Russian literary culture, but also the processes of its becoming of a mass character. This literature is also in demand in our time, because its content turns to the most important spiritual source of human existence. We have emphasized the great scientific significance of the work by O.N. Aleksandrova-Osokina, which was in the first systematic research of such a little-studied phenomenon of Russian literature as “pilgrim prose”, as well as in the introduction to the studying of “forgotten” and “unknown” writers and, at the same time, in coverage of the spiritual interests of the famous Russian classical writers (A.S. Pushkin, Yu.M. Lermontov, F.I. Tyutchev, F.M. Dostoevsky, etc.). This reviewed monograph, in our opinion, is of interest not only for philologists, but also for cultural scientists, historians, philosophers, theologians, as well as for a wide range of researchers interested in Russian spiritual literature. Further research in this field can embrace the phenomenon of pilgrimage prose after 1860.